Riesgos naturales y conservación de la arquitectura defensiva de tierra: aproximación a los daños causados por seísmos en la Alcazaba de Almería y en la muralla de La Hoya - Marcos-Cobaleda, María; Gutiérrez Carrillo, María Lourdes; Molero Melgarejo, Emilio (Universidad de Granada; Universidad Politécnica de Valencia; Patronato de la Alhambra y el Generalife, 2020)
The aim of this work is to present the results obtained in the framework of the PREFORTI Project. The particular case analysed is the damages caused by earthquakes in the medieval fortifications of Almeria and the consequences on their conservation. Almeria is a zone of important seismic activity. This particularity has caused many problems to conserve its Islamic military architecture. Within this work, we include the most important earthquakes that have affected this heritage since the late fifteenth century and the constructions damaged –to a greater or lesser extent– by them, including their specific damages and an approach to their state of conservation. Due to its importance within the military constructions, we present the case study of the Alcazaba of Almeria and the wall of La Hoya, focusing on the second one. These paradigmatic constructions were widely affected by the earthquakes since the late fifteenth century. Beyond the analysis of the damages caused by the earthquakes and the different historical restorations to mitigate them, we include the emergency measures proposed in the framework of the PREFORTI Project for its better conservation against the different risks, as well as the microzonation mapping of the natural seismicity risk for the section of the wall of La Hoya in order to delve in the study of the vulnerability of this cultural asset against this natural risk, as a mechanism for its better preventive conservation.
Natural Risks and Conservation of Rammed-earth Defensive Architecture: Approach to the Damages Caused by Earthquakes in the Alcazaba of Almeria and the Wall of La Hoya
Keywords: Arquitectura medieval - España - Almería; Fortificaciones; Almeria; Medieval fortifications; Earthquakes; Preforti projects